Sustained Delivery System for Stem Cell-Derived Exosomes - Riau, Andri K.; Ong, Hon Shing; Yam, Gary H. F.; Mehta, Jodhbir S. (Frontiers in Pharmacology, 2019)
Recent literature has ascribed that the paracrine action of stem cells is mediated by exosomes. Exosomes are nano-sized extracellular vesicles (30 nm to 100 nm) of endocytic origin that play important roles in intercellular communication. They have the ability to deliver various therapeutic effects, e.g., skin regeneration or cardiac function recovery, when applied topically or injected systemically. However, injection of exosomes has been shown to result in rapid clearance from blood circulation and accumulation of the exosomes in the liver, spleen, lung, and gastrointestinal tract can be found as early as 2 hours after injection. Topical administration of exosomes on the skin or ocular surface would suffer the same fate due to rapid fluid turnover (sweat or tears). Biodegradable or highly porous hydrogels have been utilized to load exosomes and to deliver a sustained therapeutic effect. They can also prevent the exosomes from being cleared prematurely and allow the delivery of a more localized and concentrated exosome dosage by placing the hydrogel directly at or in the proximity of the target site. In this mini-review, we elaborate on the challenges of conventional exosome administration and highlight the solution to the shortcomings in the form of exosome-incorporated hydrogels. Different techniques to encapsulate exosomes and examples of hydrogels that have been used to create sustained delivery systems of exosomes are also discussed.